Adapting living spaces an analysis of two selected lodging facility in U.P Diliman campus, Quezon City - Go, Maricris Sofia; Buencamino, Lorena M. (2006.)
Being a bed spacer herself, the researcher decided to study about two of the most common lodging facilities in the University of the Philippines Diliman. Like the researcher, occupants of these lodging spaces are mostly students. This study aimed to find out the efficiency of these living spaces for students namely, a boarding house and a bed spacing unit. The specific objectives of the study that were fulfilled are the following: determining the operative definition of a boarding house and a bed spacing unit, and evaluation of the efficiency of the selected spaces based on space function, space allowance for each occupant, and overall design of the space. It provided awareness to people as to what rates and trends in terms of living in rented spaces prevail. The study also served as a guide in determining the design considerations to provide for a boarding house or a bed spacing unit. The descriptive survey method was used in this study employing purposive sampling or the so-called deliberative as the sampling design. Observation became the most powerful tool in laying the groundwork of the study and it is definitely supported by citations from distinguished authors, surveys, and interviews with the people involved in the study. The concept of proxemics as well as general design consideration was utilized to analyze the data at hand. In representing the gathered data, schematic drawings and tabular charts were used to provide a clear understanding of the study. Significant conclusions were achieved such as: terms like "boarding house" and "apartment" were used interchangeably. The legal definition of an apartment becomes the operative definition of the boarding house. On the other hand, the practice of offering bed spacing services remain an "underground business" due to its lack of recognition by the National Building Code as well as authorities like the National Housing Authority, Housing and Land Use Regulatory Board and City Personnel Office of Quezon City. The advantages as well as disadvantages of living in these lodging facilities were also weighed. Important recommendations were provided such as the standardization of rental costs, the provision of authorized written agreements between the owner and the occupants so as to protect their rights. Finally, design solutions were given in order to give suggestions for the improvement of the occupants' living conditions in terms of the condition and design of the space.
Thesis (BID)--University of the Philippines Diliman.
Keywords: Boardinghouses -- Philippines -- Quezon City